Concentration–discharge relationships describe solute and sediment mobilization, reaction, and transport at event and longer timescales - Rose, Lucy A.; Karwan, Diana L.; Godsey, Sarah E. (Hydrological processes, 2018)
Concentration–discharge (C‐Q) relationships reflect material sources, storage, reaction, proximity, and transport in catchments. Differences in hydrologic pathways and connectivity influence observed C‐Q patterns at the catchment outlet. We examined solute and sediment C‐Q relationships at event and interannual timescales in a small mid‐Atlantic (USA) catchment. We found systematic differences in the C‐Q behaviour of geogenic/exogenous solutes (e.g., calcium and nitrate), biologically associated solutes (e.g., dissolved organic carbon), and particulate materials (e.g., total suspended solids). Negative log(C)–log(Q) regression slopes, indicating dilution, were common for geogenic solutes whereas positive slopes, indicating concentration increase, were common for biologically associated solutes. Biologically associated solutes often exhibited counterclockwise hysteresis during events whereas geogenic solutes exhibited clockwise hysteresis. Across event and interannual timescales, solute C‐Q patterns are linked to the spatial distribution of hydrologic sources and the timing and sequence of hydro‐biogeochemical source contributions to the stream. Groundwater is the primary source of stormflow during the earliest and latest stages of events, whereas precipitation and soil water become increasingly connected to the stream near peakflow. This sequence and timing of flowpath connectivity results in dilution and clockwise hysteresis for geogenic/exogenous solutes and concentration increase and counterclockwise hysteresis for biologically associated solutes. Particulate materials demonstrated positive C‐Q slopes over the long‐term and clockwise hysteresis during individual events. Drivers of particulate and solute C‐Q relationships differ, based on longitudinal and lateral expansion of active channels and changing shear stresses with increasing flows. Although important distinctions exist between the drivers of solute and sediment C‐Q relationships, overall solute and sediment C‐Q patterns at event and interannual timescales reflect consistent catchment hydro‐biogeochemical processes.